IL as the Collective Godhead ˀIlū in LB Ugarit - Tsumura, David Toshio (Journal of the American Oriental Society, 2023)
It is generally assumed that a cult of El existed in Late Bronze Age Ugarit and that the alphabetic spelling IL must refer either to the generic "god" or to the divine name El. However, such an either-or question is too simplistic when we are dealing with the multifarious nature of polytheism. In the light of Ugaritic material, which includes the liturgical texts, several "pantheon" lists, a quadrilingual vocabulary, as well as theophoric personal names, it is obvious that IL also can refer to the collective godhead Ilū. Furthermore, IL in the ritual-myth text KTU 1.23 is distinct from El in the Baal cycle. In light of several Greek and ancient Near Eastern myths of "divine engenderment," KTU 1.23 most likely deals with the motif of the collective godhead IL (ˀIlū), who impregnated two human women in order to engender two sets of divinities. Hence, the deus otiosus theory that IL in 1.23 is a "younger" El should be rejected.